2011
DOI: 10.1111/j.1365-2893.2010.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of restoration of immune responses of patients with chronic hepatitis B during lamivudine therapy: increased antigen processing and presentation by dendritic cells

Abstract: Restoration of host immunity has been reported in patients with chronic hepatitis B (CHB) after treatment with lamivudine; however, the underlying mechanisms of this treatment have not been determined. This study examined the role of antigen-presenting dendritic cells (DC) in restoration of host immunity. Circulating DC were isolated from peripheral blood of 23 patients with CHB before and 1, 3, and 12 months after starting lamivudine therapy. The non-antigen-specific proliferation of DC was assessed in alloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Without direct effects on host immunity, NAs could effectively disturb the replication circles of HBV to decrease the viral antigen load, which is also beneficial for the reconstruction of antiviral immunity. Thus, several researches have suggested that early immune restoration during NAs therapy could partly reflect and even predict the long‐term therapeutic responses . Here, for the first time, we made a thorough analysis of four CD4 + T subsets in both the cross‐sectional and longitudinal studies during chronic HBV infection, and designed several in vitro experiments to investigate the effects of reconstructed CD4 + T cells on the profibrogenic features of HSCs, which might be informative in understanding the roles of CD4 + T‐cell responses in both the host–virus interactions and the inflammation–fibrosis cross‐talks.…”
Section: Discussionmentioning
confidence: 99%
“…Without direct effects on host immunity, NAs could effectively disturb the replication circles of HBV to decrease the viral antigen load, which is also beneficial for the reconstruction of antiviral immunity. Thus, several researches have suggested that early immune restoration during NAs therapy could partly reflect and even predict the long‐term therapeutic responses . Here, for the first time, we made a thorough analysis of four CD4 + T subsets in both the cross‐sectional and longitudinal studies during chronic HBV infection, and designed several in vitro experiments to investigate the effects of reconstructed CD4 + T cells on the profibrogenic features of HSCs, which might be informative in understanding the roles of CD4 + T‐cell responses in both the host–virus interactions and the inflammation–fibrosis cross‐talks.…”
Section: Discussionmentioning
confidence: 99%
“…However, vaccines consisting of recombinant HBsAg and anti-HBs immunoglobulins could induce HBs-specific T cells efficiently since the formation of Ag-Ab immune complexes could be easily captured and taken up by DCs [96]. Although HBsAg might suppress the functions of DCs [11], HBsAg-pulsed DCs might enhance HBV-specific immune response in CHB patients [97]. …”
Section: Hbsag and Immunotherapymentioning
confidence: 99%
“…Similarly, the recovery of functional pDCs during IFN‐α therapy may also have the same predictive value 48 . A recent study further reported that lamivudine therapy is able to reduce HBV DNA to an undetectable level, but the patients may only exhibit a transient restoration of circulating DC 49 . These findings suggest that the dynamics of DC frequency and functionality are associated with the responsiveness to antiviral therapy in CHB patients, and thus have the potential to serve as prognostic markers for HBV disease progression and treatment efficacy.…”
Section: Immune Cells or Molecules Can Be Potentially Used To Predictmentioning
confidence: 95%